Coffee consumption decreases the connectivity of the posterior Default Mode Network (DMN) at rest - Picó-Pérez, Maria; Magalhães, Ricardo; Esteves, Madalena; Vieira, Rita; Castanho, Teresa C.; Amorim, Liliana; Sousa, Mafalda; Coelho, Ana; Moreira, Pedro S.; Cunha, Rodrigo A.; Sousa, Nuno (Frontiers in Behavioral Neuroscience, 2023)
Habitual coffee consumers justify their life-choice arguing that they become more alert and increase motor and cognitive performance and efficiency; however, these subjective impressions still do not have a neurobiological correlate. Using functional connectivity approaches to study resting-state fMRI data in a group of habitual coffee drinkers, we herein show that coffee consumption decreased connectivity of the posterior Default Mode Network (DMN) and between the somatosensory/motor networks and the prefrontal cortex, while the connectivity in nodes of the higher visual and the right executive control network (RECN) are increased after drinking coffee; data also show that caffeine intake only replicated the impact of coffee on the posterior DMN, thus disentangling the neurochemical effects of caffeine from the experience of having a coffee.